2014
DOI: 10.1007/s11606-014-3029-0
|View full text |Cite
|
Sign up to set email alerts
|

Low Use and Adherence to Maintenance Medication in Chronic Obstructive Pulmonary Disease in the General Population

Abstract: OBJECTIVE:We tested the hypothesis that use of and adherence to maintenance medication is low among individuals in the general population who have chronic obstructive pulmonary disease (COPD) , even in cases of severe and very severe COPD. DESIGN AND PARTICIPANTS: We identified 5,812 individuals with COPD from the Copenhagen General Population Study, and classified them according to the Global Initiative for Obstructive Lung Disease (GOLD) airflow limitation grades 1-4. Dispensing of fixed-dose combinations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
59
3
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 24 publications
8
59
3
7
Order By: Relevance
“…This effect was mitigated by increased severity of COPD symptoms, evidenced by acute inhaler use, oxygen use, and COPD-related hospitalizations, and is consistent with a prior report (30). Historically, use of and adherence to COPD maintenance medications has been suboptimal, with many individuals with COPD not receiving any maintenance medications (14,15,17). Among individuals who use COPD medications, adherence is low, which poses difficulties in medication management (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Original Researchsupporting
confidence: 83%
See 2 more Smart Citations
“…This effect was mitigated by increased severity of COPD symptoms, evidenced by acute inhaler use, oxygen use, and COPD-related hospitalizations, and is consistent with a prior report (30). Historically, use of and adherence to COPD maintenance medications has been suboptimal, with many individuals with COPD not receiving any maintenance medications (14,15,17). Among individuals who use COPD medications, adherence is low, which poses difficulties in medication management (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Original Researchsupporting
confidence: 83%
“…Historically, use of and adherence to COPD maintenance medications has been suboptimal, with many individuals with COPD not receiving any maintenance medications (14,15,17). Among individuals who use COPD medications, adherence is low, which poses difficulties in medication management (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In this study, we found that only 22% of the sample achieved adherence of at least 80%, regardless of depression status.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…1421 Treatment of comorbid illness could impact adherence and outcomes among individuals with COPD; however, few studies have examined this question. Among Medicare beneficiaries diagnosed with both COPD and depression, antidepressant treatment was associated with reduced mortality; however, receipt of depression care was not associated with fewer COPD-related hospitalizations among a similarly diagnosed cohort of veterans.…”
Section: Introductionmentioning
confidence: 99%
“…I ngebrigsten, et al 1 conducted a population-based study of patients with chronic obstructive pulmonary disease (COPD) in Denmark. Participants (n=5,812) were stratified by COPD severity and maintenance respiratory medication use was examined for 1 year.…”
mentioning
confidence: 99%